Construction of a phantom to test the performance of emission computed tomography systems - Sayed, Inayatullah Shah (2011)
It is imperative to assess/evaluate the performance of emission computed tomography (ECT) system prior to the use in clinical studies. For this purpose, a variety of test phantoms is commercially available with exactly known composition. The phantom data are used to examine and acquire prior knowledge about the capability and drawbacks of an ECT system. Data are also applied to test the accuracy of image reconstruction, processing, analysis, scatter and attenuation correction procedures. Moreover, it is used for teaching purposes, student demonstrations and in research. A novel cold regions insert, that can be placed into a cylindrical tank has been developed, which consists eight pairs of cold regions in “V” shape with different diameters and locations with respect to the wall of the phantom tank. The cold regions arrangement is similar to the hot regions of R A Carlson’s phantom. This makes the phantom distinct as compared to other commercially available phantoms. The work in this project has been done in order to further improve the design of the phantom (cold regions insert and cylindrical tank). The height of the cylindrical tank of the phantom has been raised so that an additional insert e.g., spatial resolution can be accommodated. The cover plate of the cylindrical tank has been modified and radioactivity inlet holes of cover plate are designed differently keeping in mind the radiation safety/protection considerations and for proper loading of radioactive solution into the phantom.